Single amino acid change alters the ability to specify male or female organ identity - Airoldi, Chiara A.; Bergonzi, Sara; Davies, Brendan; Coen, Enrico Sandro (Proceedings of the National Academy of Sciences - PNAS, 2010)
The molecular mechanisms underlying the developmental processes that shape living organisms provide a basis to understand the evolution of biological complexity. Gene duplication allows biological functions to become separated, leading to increased complexity through subfunctionalization. Recently, the relative contributions to morphological evolution of changes to the regulatory and/or coding regions of duplicated genes have been the subject of debate. Duplication generated multiple copies of the MADS-box transcription factor genes that play essential roles in specifying organ identity in the flower, making this evolutionary novelty a good model to investigate the nature of the changes necessary to drive subfunctionalization. Here, we show that naturally occurring variation at a single amino acid in a MADS-box transcription factor switches its ability to specify male and female reproductive organs by altering its repertoire of protein–protein interactions. However, these different developmental fates are only manifest because of an underlying variation in the expression pattern of interacting proteins. This shows that the morphological outcomes of changes to protein sequence and gene expression must be interpreted in the context of the wider regulatory network. It also suggests an explanation for the surprisingly widespread duplications of some of the floral transcription factors.